1988
DOI: 10.1136/jmg.25.12.854
|View full text |Cite
|
Sign up to set email alerts
|

Is geroderma osteodysplastica underdiagnosed?

Abstract: cm and birth weight 3030 g. Achondroplasia with rhizomelic shortening of the limbs and macrocephaly was suspected at birth and x ray films of the skeleton confirmed the diagnosis. When examined for the second time, the girl was 12 years old and 116 cm tall. Psychomotor development was normal. Clinical and radiological features were typical of achondroplasia. A normal boy was born in 1977. Case 2 (11.3), born in 1981, is the sister of case 1. The diagnosis of achondroplasia was immediately evident. At five year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 4 publications
2
22
0
2
Order By: Relevance
“…The skeletal phenotypic features observed in Gorab Prx1 tibiae are generally consistent with clinical reports on GO patients (Al-Gazali et al, 2001; Hennies et al, 2008; Hunter, 1988; Hunter et al, 1978; Lisker et al, 1979; Nanda et al, 2008; Rajab et al, 2008), who have short stature and bowed long bones (tibia and femur) and often experience bone fractures (Rajab et al, 2008). Our current results from tibial morphological measures are in agreement with previous observations of Steiner et al 2015 (Steiner et al, 2015) showing that Gorab deficiency leads to a retardation of long bone growth and a dramatic reduction in trabecular and cortical bone volumes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The skeletal phenotypic features observed in Gorab Prx1 tibiae are generally consistent with clinical reports on GO patients (Al-Gazali et al, 2001; Hennies et al, 2008; Hunter, 1988; Hunter et al, 1978; Lisker et al, 1979; Nanda et al, 2008; Rajab et al, 2008), who have short stature and bowed long bones (tibia and femur) and often experience bone fractures (Rajab et al, 2008). Our current results from tibial morphological measures are in agreement with previous observations of Steiner et al 2015 (Steiner et al, 2015) showing that Gorab deficiency leads to a retardation of long bone growth and a dramatic reduction in trabecular and cortical bone volumes.…”
Section: Discussionsupporting
confidence: 85%
“…Gerodermia osteodysplastica (GO, MIM#231070) is a hereditary segmental progeroid disorder (Al-Gazali et al, 2001; Hennies et al, 2008; Nanda et al, 2008; Rajab et al, 2008), one of the few monogenic disorders other than osteogenesis imperfecta that has pronounced osteoporosis and fractures already in childhood (Hunter, 1988; Lisker et al, 1979; Nanda et al, 2008). Individuals with GO also have a prematurely aged appearance with wrinkled skin and generalized connective tissue weakness (Al-Bughaili et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were made previously [Gazit et al, 1973;Fitzsimmons et al, 1985]. Hunter [1988] suggested that GO may be underdiagnosed, which may be also be true for WSS. We suggest considering WSS and GO in adult patients who tend to look ''older than their age'' and who have early onset osteopenia, brittle bones and scoliosis.…”
Section: Discussionsupporting
confidence: 84%
“…In this study we investigated the molecular cause of gerodermia osteodysplastica (also: geroderma osteodysplasticum, GO; OMIM 231070), a rare autosomal recessive disorder characterized by lax, wrinkled skin, joint laxity, and a typical face with a prematurely aged appearance. Skeletal signs include severe osteoporosis leading to frequent fractures, malar and mandibular hypoplasia, and a variable degree of growth retardation 1,2 . According to the current definition, GO can be regarded as a segmental progeroid disorder involving bone and skin 3 .…”
mentioning
confidence: 99%